PERIODISASI PERKEMBANGAN HUKUM ISLAM DARI JAHILIYAH HINGGA MADINAH - Awin Haqqol Walid (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2022)
Humans are creatures who cannot live alone without the help of others in their daily activities. Human activities from time to time are increasingly diverse, ranging from things that are small to large. All human activities need to be regulated so as not to interfere with human activities or even other creatures. The laws that govern human activity are studied in this study. There are many good human behaviors that can be studied both in terms of economics, law, politics, and culture. However, this study focuses more on Islamic legal activities from the period of ignorance to Medina which are studied through historical and normative approaches. The stages of Jahiliyah, Mecca, and Medina have their own differences in the development of the law. Just as during the Jahilyah period, the applicable law was known, namely, who was strong, he got the position, Mecca was identical with the cultivator of faith and Medina was known as the period of cultivating and developing Islamic law.